In vitro release of arachidonic acid metabolites, glutathione peroxidase, and oxygen-free radicals from platelets of asthmatic patients with and without aspirin intolerance. Issue 5 (May 1995) - Plaza, V; Prat, J; Rosellò, J; Ballester, E; Ramis, I; Mullol, J; Gelpí, E; Vives-Corrons, J L; Picado, C
Abstract : BACKGROUND--An abnormal platelet release of oxygen-free radicals has been described in acetylsalicylic acid (aspirin)-induced asthma, a finding which might suggest the existence of an intrinsic, specific platelet abnormality of arachidonic acid metabolism in these patients. The objective of this study was to evaluate platelet arachidonic acid metabolism in asthmatic patients with or without intolerance to aspirin. METHODS--Thirty subjects distributed into three groups were studied: group 1, 10 healthy subjects; group 2, 10 asthmatic patients with aspirin tolerance; and group 3, 10 aspirin-intolerant asthmatics. Platelets were isolated from blood, preincubated with 3H-arachidonic acid for 30 minutes and then incubated for 10 minutes with platelet activating factor (PAF) and aspirin. Cyclo-oxygenase (thromboxane, PGE2, PGF2 alpha, and HHT) and lipoxygenase (12-HETE) arachidonic acid metabolites were measured by high pressure liquid chromatography. Release of oxygen free radicals after incubation with PAF and aspirin was measured by chemiluminescence. Platelet levels of glutathione peroxidase (GSH-Px) were also measured using spectrophotometry. RESULTS--Platelets from aspirin-intolerant asthmatic patients produced higher quantities of arachidonic acid metabolites than the control group at baseline conditions. This increase was significant only for lipoxygenase products. No differences were found amongst the three groups in the response of arachidonic acid metabolism to PAF and aspirin. Incubation with aspirin but not with PAF caused an increase in oxygen-free radical production in aspirin-intolerant patients whereas in aspirin-tolerant patients PAF, rather than aspirin, was the more potent stimulus for oxygen-free radical production. No differences in GSH-Px levels were found amongst the three groups. CONCLUSIONS--These results suggest that the platelet lipoxygenase pathway is activated in aspirin-intolerant patients and that the production of oxygen-free radicals may differentiate aspirin-tolerant from aspirin-intolerant asthmatic subjects. Our study, however, does not support the hypothesis that an increase in lipoxygenase products may be responsible for oxygen-free radical production. Moreover, a lowered platelet GSH-Px activity does not seem to be involved in this phenomenon.